Distribution Patterns (7B Rule) and Characteristics of Large Congenital Melanocytic Nevi: A Retrospective Cohort Study in China - Wang, Huijing; Wang, Wei; Lu, Jun; Gu, Yihui; Cui, Xiwei; Wei, Chengjiang; Ren, Jieyi; Gu, Bin; Wang, Zhichao; Li, Qingfeng (Frontiers in Medicine, 2021)
Large congenital melanocytic nevus has a high risk of malignancy. However, few studies have summarized its characteristics, treatments, outcomes and malignancy incidence in Chinese patients. This paper reviews a retrospective cohort study evaluating 1,171 patients from Shanghai Ninth People's Hospital between 1 January 1989 and 31 August 2019 using electronic medical records and phone calls to collect clinical and pathological data in which 133 patients were diagnosed with a large congenital melanocytic nevus. Three patients relapsed, and none developed melanoma among the qualified patients. Besides, a new “7B” rule for distribution patterns of large congenital melanocytic nevi was proposed, including bonce, bolero, back, bathing trunk, breast/belly, body extremity, and body. The most common distribution pattern of large congenital melanocytic nevi was bonce, and all blue nevi distributed as bonce. Statistical analysis showed a significant difference (P = 0.0249) in the “7B” patterns between the melanocytic nevus and the neuronevus. In conclusion, the malignancy rate of large congenital melanocytic nevi is much lower in China than in other regions and people of other races. The pathology of large congenital melanocytic nevus may decide its “7B” distribution pattern.